Comparison of olanzapine-induced weight gain and metabolism abnormalities between topiramate and vitamin C in patients with schizophrenia: a preliminary study - Zhang, Jinling; Chen, Shu; Chen, Jia; Zhang, Handi; Rao, Wen-Wang (Frontiers in Psychiatry, 2023)
Background: Topiramate (TPM) may reduce olanzapine (OLZ)-related weight gain and metabolism abnormalities in patients with schizophrenia. However, differences in the efficacy of OLZ-related weight gain and metabolism abnormalities between TPM and vitamin C(VC) are not clear. This study aimed to investigate whether TPM is more effective than VC in reducing OLZ-induced weight gain and metabolic abnormalities in patients with schizophrenia and explore their patterns. Methods: This was a 12-week longitudinal comparison study in OLZ-treated patients with schizophrenia. Twenty-two patients who received OLZ monotherapy plus VC treatment (OLZ+VC group) was matched to 22 patients who received OLZ monotherapy plus TPM treatment (OLZ+TPM group). Body mass index (BMI) and metabolism indicators were measured at baseline and 12-weeks follow-up. Results: A significant difference in triglyceride (TG) levels at different time points (pre-treatment: F=7.89, P=0.008; 4-weeks treatment: F=13.19, P=0.001; 12-weeks treatment: F=54.48, P<0.001) was found. Latent profile analysis demonstrated that a 2-class model for OLZ+TPM group (high vs. low BMI in the first 4 weeks) and OLZ+VC group (high vs. low), respectively. Conclusion: Our findings suggested that TPM could better mitigates OLZ-induced increase in TG levels. The trajectories of change also differed in all metabolic indexes over time between the two groups.